Development of a regional ocean model for New Zealand - G. J. Rickard; M. G. Hadfield; M. J. Roberts (New Zealand Journal of Marine and Freshwater Research, 2005)
A regional ocean model with a horizontal resolution of 1/6° encompassing the New Zealand Exclusive Economic Zone is described. The regional model successfully downscaled solutions from a high resolution, global, coupled model HadCEM. Transport estimates from the global and regional models were compared with observations, and both models supported largely consistent, climatological mean solutions. The regional model used monthly mean forcing at the surface. Nevertheless, the regional model eddy kinetic energy (EKE) spatial patterns compared favourably with long‐term mean satellite altimetric estimates, although the modelled background EKE amplitudes were much lower than observed. A series of permanent eddies associated with the western boundary current system around the top of the North Island of New Zealand were reproduced, and an eddy adjacent to Norfolk Ridge was identified in both the global and regional models. The western boundary current system around the North Island of New Zealand and the associated eddies were the most sensitive components of the model solutions, being influenced by initial conditions, wind forcing, and the model domain size.